THE CONSTRUCTION OF PROFESSIONAL IDENTITY IN PSYCHOLOGY: CONTEMPORARY CHALLENGES AND THE INTEGRATION BETWEEN THEORY AND PRACTICE - de Oliveira Neto, Francisco José (Seven Editora, 2026)
The literature on psychology training in Brazil has highlighted its historical and institutional challenges; however, the articulation between epistemological fragmentation, the hegemony of formative practices, and the expansion of higher education under market-oriented logics remains insufficiently explored. This article critically examines the contemporary determinants of psychology training, with emphasis on the disjunction between theory and practice, the centrality of traditional clinical approaches, and the effects of the commodification of higher education. A theoretical-analytical approach is adopted, grounded in the historical-critical tradition, articulating a bibliographic review of key authors in Brazilian social psychology and education with the analysis of data from the Higher Education Census (MEC/INEP). The analysis demonstrates that the dissociation between theory and practice constitutes an epistemological cleavage that undermines the development of critical praxis; that the hegemony of clinical training restricts fields of practice, reinforces the individualization of psychological suffering, and limits interdisciplinary engagement; and that the quantitative expansion of higher education, driven by market criteria, produces training precarization, weakens research, and reconfigures pedagogical relations. These processes operate interdependently, expressing the structural determinations that shape professional training and its social commitment. It is concluded that overcoming these limitations requires the reconfiguration of the training model, with emphasis on the integration of theory and practice, the strengthening of research, and the construction of a critical, ethical, and socially engaged formation aligned with the Brazilian context.